Essays on FDI, growth, and political instability in developing countries - Williams, Kevin (2010)
Foreign direct investment (FDI) plays an important role in development strategies in developing countries. In particular, policy makers in developing countries and development agencies alike believe that FDI is growth enhancing, as suggested by their policy stand (in particular, promoting measures to facilitate and attract FDI). FDI is different from other types of capital flows as it involves not only the capital itself, but also transfers in the form of technology diffusion and skills, managerial expertise and know-how, and the introduction of new processing methods (Rodrik and Subramanian, 2008). These serve to modernize the recipient economy and support productivity gains, which in turn are expected to improve growth performance.